(untitled) (Gestión y Gerencia, 2018)
This research is a theoretical work based on documentary design, which aims to present various conceptual elements around entrepreneurship, the profile of an entrepreneur, characteristics of the Venezuelan entrepreneur, analyze the relationship between entrepreneurship and endogenous development, as well as examine the role of the university in the generation of entrepreneurial capacities, all within the political, economic and social context of Venezuela. Among the results, highlight the drastic change that the profile of the Venezuelan entrepreneur has had in the last two decades; the incipient promotion of entrepreneurial activity in Venezuelan universities; hence the need to overcome the current model of university training for "employees" by one that privileges the training of "entrepreneurs-innovators", adapted to the socio-productive needs of the country. The formation of entrepreneurs is emerging as a commitment that the university must assume from the research, the extension and a curriculum transversality; but that also requires a state policy that favors entrepreneurial activity and an environment convenient for creation and the consolidation of new ventures.